(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Acute diseases of the abdominal organs remain one of the leading causes of emergency hospital admissions and urgent surgical interventions worldwide. Particular diagnostic difficulties arise in patients with an unclear or atypical clinical presentation, when standard diagnostic methods—clinical assessment, laboratory investigations, ultrasonography, and computed tomography—may be insufficient to establish an accurate diagnosis in a timely manner. Diagnostic uncertainty and delayed decision-making often result in disease progression, increased risk of complications, and poorer clinical outcomes.